2017
DOI: 10.23736/s0022-4707.16.06272-1
|View full text |Cite
|
Sign up to set email alerts
|

Hand grip strength and anthropometric characteristics in Italian female national basketball teams

Abstract: The motto of the Olympic Games is Citius, Altius, Fortius which is Latin for ''Faster, Higher, Stronger''. It is a call to all competitors, not just the elite, to engage in training strategies that enhance muscular fitness and physical prowess. Today, global health recommendations aim to increase the number of children and adolescents who participate in resistance training activities. Regular participation in a developmentally appropriate resistance training program that is purposely designed to enhance neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…In this study, handgrip strength correlated with many factors: gender, age, height, weight, opposite side of handgrip strength, both sides of LEP, area of skeletal muscle at L3, area of the psoas muscle, PMI, walking speed, walking steps, and intermittent claudication. Other studies had shown handgrip strength positively correlating with LEP [16], height [17,18], weight [18], and BMI [17]. Lauretani et al showed that handgrip strength declines considerably with aging [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, handgrip strength correlated with many factors: gender, age, height, weight, opposite side of handgrip strength, both sides of LEP, area of skeletal muscle at L3, area of the psoas muscle, PMI, walking speed, walking steps, and intermittent claudication. Other studies had shown handgrip strength positively correlating with LEP [16], height [17,18], weight [18], and BMI [17]. Lauretani et al showed that handgrip strength declines considerably with aging [19].…”
Section: Discussionmentioning
confidence: 99%
“…The anthropometric profile of an athlete is related to sports performance (Norton et al, 1996), and in the youth categories, it can help recruiters/coaches in directing an athlete towards one sport rather than another, or in a team sport, it can help in choosing the right role (Pizzigalli et al, 2017;Sterkowicz-Przybycien´ et al, 2019;Bernal-Orozco et al, 2020). According to Cagnazzo & Cagnazzo (2009), athletes with high stature (184-194 cm) are directed towards sports in which height takes on a selective value for sports performance (e.g., basketball, volleyball).…”
Section: Discussionmentioning
confidence: 99%
“…However, although anthropometric evaluations of the upper extremities were conducted in the present study, an analysis to determine muscle quality was not performed since the study had a different purpose. Therefore, assessing muscle quality by calculating only the handgrip and anthropometric parameters—such as forearm length [ 28 ], hand length [ 8 ], or body composition [ 29 ]—could be unspecific and imprecise. Consequently, to obtain a specific and accurate assessment of muscle quality, we suggest using strength, power, and anthropometry tests for each body segment.…”
Section: Discussionmentioning
confidence: 99%